The Development Guidelines for Teacher in Creative Learning Management for Schools under the Maha Sarakham Primary Education Service Area Office 3: The Development Guidelines for Teacher in Creative Learning Management for Schools under the Maha Sarakham Primary Education Service Area Office 3 - Klangphimai, Nicksant; Phoojomjit, Pongphop (RATANABUTH JOURNAL, 2023)
The purposes of this research were to 1) study the current and the desirable state of developing for teacher in creative learning management for schools under the Maha Sarakham primary education service area office 3. 2) study the development guidelines for teacher in creative learning management for schools under the The Maha Sarakham primary education service area office 3. The research process was divided to 2 phases: Phase 1 ; to study the current and the desirable state of developing for teacher in creative learning management. The sample group used in the research was administrators and teachers, 278 people, by stratified sampling. The research tool was a questionnaire, confidence of the whole .78. The statistics used for data analysis were mean, standard deviation. Phase 2; to study the development guidelines for teacher in creative learning management for schools under the Maha Sarakham primary education service area office 3. The target group is 7 experts. The research tool was interview form, Data analysis by content analysis. The research results were found that The current state in overall was high average and the desirable state in overall was in the highest level. The priority need rank from high to low level was 1) Promoting creative processes 2) learning management for learner’s nature, potential and needs of learners 3) learning management for practice and experience. Guidelines for teacher development in creative learning management Include, 1) Promoting creative processes, 2 guidelines 2)learning management for learner’s nature, potential and needs of learners, 2 guidelines 3)learning management for practice and experience, 2 guidelines